Pelatihan Pembuatan Snack Semprit/Pret Khas Aceh Kaya Antioksidan Dengan Penambahan Pasta Buah Bit dan Buah Naga Merah di Panti Asuhan Yayasan Islam Media Kasih, Banda Aceh - Irmayanti, Irmayanti; Anwar, Chairil (Politeknik Negeri Madiun, 2020)
At present there is a large variety of regional specialty food products that are still made with original flavors and use artificial coloring, whereas in fruits and vegetables there are many natural coloring and antioxidant contents. Pret cakes circulating in Aceh are still original, so it is necessary to diversify the product by adding red dragon fruit paste and beets. In addition to adding nutritional value, antioxidant components, the addition of red dragon fruit paste and for this beet can provide an attractive color to pret cake products. Pret cake can be used as a snack or even as one of the products for entrepreneurship, because pret cake is a traditional one from Aceh. This activity is expected to be able to provide new knowledge and ideas as well as to practice making Aceh's unique pret cake with variations in the addition of beet paste and red dragon fruit which are rich in antioxidants and natural coloring to children and adolescents, orphans, orphans and the needy residents of the Islamic Foundation Orphanage Media Kasih Banda Aceh in processing typical Acehnese snack cakes that are more nutritious and varied and can increase the economic value of these pretake products.